Salt Production Activities in Izmir Çamaltı Saltern and in Turkey (1923-1950) / İzmir Çamaltı Tuzlası ve Türkiyede Tuz Üretimi Çalışmaları (1923-1950) - Yurtoğlu, Nadir (Journal of History Culture and Art Research, 2018)
Abstract This study deals with salt production activities in Izmir Çamaltı Saltern and in Turkey in the Republic period and their contributions to economy. Data has been obtained by scanning the literature. The subject is limited to and discussed under the title of salt production activities in Izmir Çamaltı Saltern and in Turkey in the period of Republican People’s Party (CHP) (1923-1950). Evaluations have been made based on numeric data in discussing the salt production activities in Izmir Çamaltı Saltern and in Turkey. The gap in the literature about the research subject has been filled through use of primary sources such as Republic archive documents, official publications, journals of laws, journals of official reports, proceedings of memorandum, official gazettes, statistical data, Ayın Tarihi journal (government’s dating publication), and articles from the magazines of the period. The relevant evaluations have been made considering the production processes in Turkey and those in the leading countries in the world about salt production. It has been found out that salt production, sales, and export were monopolized by the state with the General Directorate of Salt Monopoly set up on 1 June 1927 with its center in Ankara. With the modernization of Çamaltı Saltern and other facilities established from that date on, the amount of salt production in Turkey and salt export to other countries increased, thereby making substantial contributions to the national economy. Öz Bu araştırmada Cumhuriyet döneminde İzmir Çamaltı Tuzlası ve Türkiye’de tuz üretimi faaliyetleri ile bunun ekonomiye olan katkıları ele alınmıştır. Veriler literatür taraması yoluyla elde edilmiştir. Konu, Cumhuriyet Halk Partisi (CHP) döneminde Çamaltı Tuzlasında ve Türkiye’de tuz üretimi faaliyetleri (1923-1950) ile sınırlandırılmış ve bu başlık etrafında incelenmiştir. Çamaltı tuzlası ve Türkiye’de tuz üretimi çalışmaları ele alınırken sayısal veriler üzerinde değerlendirmeler yapılmıştır. Araştırmanın konusu hakkında literatürde yer alan boşluklar Cumhuriyet arşivi belgeleri, resmi yayınlardan kanunlar ve tutanak dergileri, zabıt ceridesi, resmi gazete, istatistik verileri, ayın tarihi ve dönemin süreli yayınlarından olan dergilerinin makaleleri gibi birincil kaynakların kullanılması yoluyla tamamlanmıştır. Çalışmanın konusu incelenirken dönemin Türkiye’si ile dünyanın tuz üretimi konusunda önde gelen ülkelerin üretim süreçleri göz önüne getirilerek değerlendirmeler yapılmıştır. Çalışmada elde edilen sonuç şudur: 1 Haziran 1927 tarihinde merkezi Ankara olarak kurulan Tuz İnhisarı Umumi Müdüriyeti ile tuz üretimi, satışı ve ihracatı devlet tekeline alınmıştır. Bu tarihten itibaren Çamaltı Tuzlasının modernleştirilmesi ve kurulan tesisleri sayesinde Türkiye’de tuz üretimi ve dış ülkelere yapılan tuz ihracatı miktarı artırılmış bu suretle ülke ekonomisine önemli katkılar sağlanmıştır.